2018
DOI: 10.1101/261917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Automated Bayesian Pipeline for Rapid Analysis of Single-Molecule Binding Data

Abstract: Single-molecule binding assays enable the study of how molecular machines assemble and function. Current algorithms can identify and locate individual molecules, but require tedious manual validation of each spot. Moreover, no solution for highthroughput analysis of single-molecule binding data exists. Here, we describe an automated pipeline to analyze single-molecule data over a wide range of experimental conditions. We benchmarked the pipeline by measuring the binding properties of the well-studied, DNA-guid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Experimentally, one could further investigate the nature of intersegmental transfer through a combined tweezer-fluorescence single-molecule assay, where forces strong enough to pull on entropically coiled ssDNA can be applied 17,37 . Furthermore, theoretical modelling and additional experiments are required in order to establish to what extent partitioning the search modes on different length scales will allow nucleic-acid-guided proteins to optimize the search process [52][53][54][55] since the absence of cooperative binding was recently reported for another Ago system 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, one could further investigate the nature of intersegmental transfer through a combined tweezer-fluorescence single-molecule assay, where forces strong enough to pull on entropically coiled ssDNA can be applied 17,37 . Furthermore, theoretical modelling and additional experiments are required in order to establish to what extent partitioning the search modes on different length scales will allow nucleic-acid-guided proteins to optimize the search process [52][53][54][55] since the absence of cooperative binding was recently reported for another Ago system 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that certain DNA/RNA-guided proteins interact with DNA through non-specific electrostatic interactions [21][22][23] , but the strength of these interactions and their behavior on roadblocks and secondary structures is not understood. Since these interactions are typically short-ranged [24][25][26] and short-lived 14,21,23,[26][27][28][29] , a method offering high spatiotemporal resolution is required to study these interactions. Here we make use of single molecule Förster Resonance Energy Transfer (FRET) to elucidate the mechanism of ssDNA target search by a mesophilic Ago from the bacterium Clostridium butyricum (CbAgo).…”
mentioning
confidence: 99%
“…where the posterior is assumed to be a multivariate Gaussian distribution centered at the (15,36). In addition to these benefits, the real power of VB inference methods is that they also provide an estimate of the true evidence (in the form of the ELBO).…”
Section: The Likelihood: How An Experiments Relates To a Modelmentioning
confidence: 99%
“…Practically, this means that, at some point during an investigation, a decision must be made about what the 'best' model for the phenomenon being studied should be in order to inform upon other phenomena. In Section 3.5, we discussed how the evidence, ({ }| ), quantifies the predictive power of a model, and showed how Bayesian-inference based methods, such as vbFRET (2) and others (13,15,(27)(28)(29)(30)(31)(35)(36)(37), can utilize the maximum evidence approach to choose the 'best' model for the data. The maximum evidence approach, however, fails to account for the uncertainty from the limited amount of data collected during an experiment.…”
Section: Model Selection: Determining the Best Model Using Probabilitmentioning
confidence: 99%
“…Note that at the conceptual level, FISIK is not limited to using indirect inference for stochastic model calibration. Other methods, such as Bayesian inference (28,29), including approximate Bayesian computation (30)(31)(32), are expected to be equally applicable.…”
Section: Overall Workflow Of Fisikmentioning
confidence: 99%